Neurological Physical Therapy 2017
DOI: 10.5772/67471
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Motor Imagery on Spinal Motor Neuron Excitability and Its Clinical Use in Physical Therapy

Abstract: We investigated the influence of the imagined muscle contraction strengths on spinal motor neuron excitability in healthy volunteers. F-wave was used for assessing spinal motor excitability. The F-waves during motor imagery (MI) under 10, 30, 50, 70, and 100% maximal voluntary contractions (MVCs) were compared. Furthermore, we investigated changes of the F-waves during motor imagery for 5min. Motor imagery under 10, 30, 50, 70, and 100% maximal voluntary contractions can increase spinal motor neuron excitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 52 publications
(77 reference statements)
2
10
1
Order By: Relevance
“…The imagined muscle contraction did not affect the change of the sympathetic nerve activity. This is very similar with the result of the spinal motor neuron excitability during MI at various imagined muscle contraction strengths [24][25][26]28]. If central command during MI affects the sympathetic nerve activity via the corticospinal pathway, the imagined muscle contraction strength may affect the sympathetic nerve activity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The imagined muscle contraction did not affect the change of the sympathetic nerve activity. This is very similar with the result of the spinal motor neuron excitability during MI at various imagined muscle contraction strengths [24][25][26]28]. If central command during MI affects the sympathetic nerve activity via the corticospinal pathway, the imagined muscle contraction strength may affect the sympathetic nerve activity.…”
Section: Discussionsupporting
confidence: 79%
“…The F/M amplitude ratio during MI under 10, 30, and 50% MI conditions was significantly greater than that at rest (10% MI vs. Rest, 50% MI vs. Rest, **p < 0.01; 30% MI vs. Rest, *p < 0.05) ( Tables 1-3). The F/M amplitude ratio during MI under 70% MI condition was tended to be increased than that at rest (p ≒ 0.082) ( Table 4) The relative values of the persistence, F/M amplitude ratio, and latency did not exhibit significant differences among all MI conditions ( Our previous works [24][25][26] suggested that MI of isometric thenar muscle activity at 10, 30, 50, and 70% MVC can facilitate the spinal motor neuron excitability. However, the imagined muscle contraction strength did not influence on change of the spinal motor neuron excitability.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In our previous studies, duration of MI was 1 min [23][24][25][26]. However, Driskell et al [45] indicated that 10-15 min may be appropriate for duration of MI training session.…”
Section: The Influence Of Duration Of MI On the Excitability Of Spinamentioning
confidence: 99%
“…Previously, we investigated the influence of MI of isometric thenar muscle activity on the excitability of spinal motor neurons [18,[23][24][25][26]. Previous results indicated that the MI of thenar muscle activity at 50% MVC can increase the excitability of spinal motor neurons.…”
Section: The Influence Of Imagery Strategy On the Excitability Of Spimentioning
confidence: 99%